TINJAUAN MUSIKAL MATERI LOMBA KARAWITAN TINGKAT SEKOLAH DASAR 01 SURAKARTA - Isti Kurniatun (Institut Seni Indonesia Surakarta, 2010)
Education, Youth and Sport Service of Surakarta holds karawitan festival for Elementary Schools once a year. The problem of the festival is that the pieces of the festival does not match with the physical and psychic competence of children. The pieces of the festival (instrumentation and vocalization) is more suitable for adults than children. Beside that, the gendhing (melody) and larasan (pitch) do not come up to a child's competence. This becomes a problem for the children, teachers and instructors. This research aims at finding out the form and garap of the matter of karawitan festival for Elementary Schools and how the pieces were arranged. In addition, it aims at offering a solution that can be taken into consideration in arranging the future pieces of the festival in order that the pieces are in accordance with children's physical and psychic need and competence. The approach used in this research is a musical, psychological, and social one. The main objective of the art festival in